Kinetics of interface state-limited hole injection in alpha-naphthylphenylbiphenyl diamine (alpha-NPD) thin layers - Garcia-Belmonte, Germa; Bisquert, Juan; Bueno, Paulo R. [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP]; Castro, F. A. (Elsevier B.V. Sa, 2009)
Injection-limited operation is identified in thin-film, alpha-NPD-based diodes. A detailed model for the impedance of the injection process is provided which considers the kinetics of filling/releasing of interface states as the key factor behind the injection mechanism. The injection model is able to simultaneously account for the steady-state, current-voltage (J-V) characteristics and impedance response. and is based on the sequential injection of holes mediated by energetically distributed surface states at the metal-organic interface. The model takes into account the vacuum level offset caused by the interface dipole, along with the partial shift of the interface level distribution with bias voltage. This approach connects the low-frequency (similar to 1 Hz) capacitance spectra, which exhibits a transition between positive to negative values, to the change in the occupancy of interface states with voltage. Simulations based on the model allow to derive the density of interface states effectively intervening in the carrier injection (similar to 5 x 10(12) cm(-2)), which exhibit a Gaussian-like distribution. A kinetically determined hole barrier is calculated at levels located similar to 0.4 eV below the contact work function. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Organic light-emitting diodes; Injection-limited current; Metal-organic interfaces; Capacitance